2015
DOI: 10.1039/c4cc07119k
|View full text |Cite
|
Sign up to set email alerts
|

A radical spin on viologen polymers: organic spin crossover materials in water

Abstract: A polymer containing viologen radical cation monomer units is shown to reversibly switch between paramagnetic and diamagnetic states via non-covalent host-guest interactions or temperature control in water. Cycling between diamagnetic and paramagnetic forms is accompanied by changes in optical and magnetic properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 46 publications
1
25
0
Order By: Relevance
“…1 This radical dimerization can be an annoyance when attempting to make ferromagnetic plastics, but is an attractive feature when using these radicals as building blocks for stimuli responsive materials, dynamic covalent assemblies, chemical sensors with optical or magnetic resonance contrast, or organic spin-crossover materials. [2][3][4][5][6][7][8][9][10] A wealth of literature on such meta-stable radical species shows that they form either weak sigma dimers or multi-centered pi dimers (pimers). 11,12 The radical-radical bond found in these pimers is fascinating for its unusual multicenter covalent bonding pattern that brings the atoms closer than the van der Waals radii but much longer than a conventional two-atom bond (>2.8 Å), while straddling the knife edge between van der Waals interactions and conventional chemical bonds in strength and properties.…”
Section: Introductionmentioning
confidence: 99%
“…1 This radical dimerization can be an annoyance when attempting to make ferromagnetic plastics, but is an attractive feature when using these radicals as building blocks for stimuli responsive materials, dynamic covalent assemblies, chemical sensors with optical or magnetic resonance contrast, or organic spin-crossover materials. [2][3][4][5][6][7][8][9][10] A wealth of literature on such meta-stable radical species shows that they form either weak sigma dimers or multi-centered pi dimers (pimers). 11,12 The radical-radical bond found in these pimers is fascinating for its unusual multicenter covalent bonding pattern that brings the atoms closer than the van der Waals radii but much longer than a conventional two-atom bond (>2.8 Å), while straddling the knife edge between van der Waals interactions and conventional chemical bonds in strength and properties.…”
Section: Introductionmentioning
confidence: 99%
“…The equilibrium between monomeric and pimeric species of viologens have been investigated not only to construct supramolecular structures, but also in view of applications in electrochromic devices, as well as spintronics and data‐storage devices: the monoreduced monomer is paramagnetic and the pimer is diamagnetic…”
Section: Introductionmentioning
confidence: 99%
“…Other examples of reversible solution dimerization in stable neutral free radicals have been reported in the phenalenyl family and in dithiadiazolyl radicals, including the dimerization of metal coordinated 4‐(2′‐pyridyl)‐1,2,3,5‐dithiadiazolyl radical (Scheme ) . Winter and co‐workers have described π‐dimer formation through host–guest interactions in solutions containing a viologen diradical cation . The well‐known galvinoxyl radical (Scheme ) and aza‐analogue are also known to dimerize in the solid‐state and have interesting temperature dependent magnetic profiles .…”
Section: Methodsmentioning
confidence: 99%
“…[14][15][16][17][18][19][20] Winter and co-workersh ave described pdimerf ormation through host-guesti nteractions in solutions containing av iologen diradical cation. [21][22][23] The well-known galvinoxyl radical( Scheme 1) anda za-analogue are also known to dimerize in the solid-state and have interesting temperature dependentm agnetic profiles. [24] Solution EPR studies of galvinoxyl radicala tdifferent temperatures have revealed behavior consistentw ith dimerization; however,t he nature of the diamagnetic species is unclear.…”
mentioning
confidence: 99%